2017
DOI: 10.18388/abp.2017_1496
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria stress response to preservation processes in the beverage and juice industry

Abstract: In this review we summarize stress factors that affect the lactic acid bacteria (LAB) and cause different molecular stress responses. LAB belong to a group of bacteria that is very widespread in food and beverages. They are present, and desired, in fermented products like yogurts, cheese, vegetables, meat or wine. In most of them, LAB are providing positive sensory and nutritive features. However, as harmless and desired microbes in one product, LAB can cause spoilage and a bad taste of others, especially in j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 63 publications
0
30
0
2
Order By: Relevance
“…Previous studies have indicated that induction of onecomponent regulatory systems (e.g., GroES-GroEL and DnaK-DnaJ) is related with acid, ethanol, cold, osmotic, starvation, and temperature stresses (Sugimoto et al 2008). DnaK was first found in heat stress in E. coli (Arsene et al 2000), but it can also be overexpressed under salt stress (Bucka-Kolendo and Sokolowska 2017). In this study, the genes encoding one-component regulatory systems DnaK-DnaJ and GroES-GroEL were identified in L. plantarum D31 (D7Y65_09835 to D7Y65_ 09830, D7Y65_06915 to D31_D7Y65_06920) and T9 genomes (D7Y66_08080 to D7Y66_08075, D7Y66_03635 to D7Y66_15720), respectively.…”
Section: Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that induction of onecomponent regulatory systems (e.g., GroES-GroEL and DnaK-DnaJ) is related with acid, ethanol, cold, osmotic, starvation, and temperature stresses (Sugimoto et al 2008). DnaK was first found in heat stress in E. coli (Arsene et al 2000), but it can also be overexpressed under salt stress (Bucka-Kolendo and Sokolowska 2017). In this study, the genes encoding one-component regulatory systems DnaK-DnaJ and GroES-GroEL were identified in L. plantarum D31 (D7Y65_09835 to D7Y65_ 09830, D7Y65_06915 to D31_D7Y65_06920) and T9 genomes (D7Y66_08080 to D7Y66_08075, D7Y66_03635 to D7Y66_15720), respectively.…”
Section: Stress Responsementioning
confidence: 99%
“…LAB chosen for commercial purposes must challenge adverse conditions encountered in industrial processes, such as heat, cold, acidity, and high concentrations of NaCl (Bucka-Kolendo and Sokolowska 2017). Many fermented food are made with the salt, by which osmotic stress is often a significant challenge for microorganisms surviving in fermentation processes (El-Gendy et al 1983;Yamani et al 1998;Prasad et al 2003;Rao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on the response of lactic acid bacteria (LAB) to stress caused by HHP are focused on the changes in the structure, metabolism, growth and viability of the cells [2][3][4][5]. As reported previously [6], HHP can influence bacterial proteome and induce protein conformational changes. The increase in the pressure can lead to the reduction in the permeability of the cell membrane and change in the conformation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…When applied as industrial fermentation factories or in fermented foods, LAB inevitably encounter organic acid stresses, which are primarily originated from LA ( Wang et al, 2018 ). Many methodologies have been employed to combat the challenges induced by LA stress as well as to improve innate LA resistance in LAB, such as intracellular microenvironment and cell membrane engineering, adaptive evolution, and extracellular protective supplementation ( Zhang et al, 2012 ; Wu et al, 2014 ; Bucka-Kolendo and Sokołowska, 2017 ). Also, owing to their broad utilization and perceived host beneficial effects in foods ( Mathur et al, 2020 ), modern applications of LAB in foods request sustainable bacterial survivability and viability in both food matrix and host GI track, which, unsurprisingly, ask for solid acid resistance from the feature LAB strains.…”
Section: Discussionmentioning
confidence: 99%